Answer:
<em>The equation of the Parabola</em>
<em>(y - 6 )² = 8 (x -6)</em>
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given directrix x = 4
we know that x = h - a = 4
h -a = 4 ...(i)
Given Focus = ( 8,6)
we know that the Focus of the Parabola
( h + a , k ) = ( 8,6)
comparing h + a = 8 ...(ii)
k = 6
solving (i) and (ii) and adding
h - a + h+ a = 8 +4
2 h = 12
h =6
Put h = 6 in equation (i)
⇒ h - a =4
⇒ 6 - 4 = a
⇒ a = 2
<u><em>Step(ii):-</em></u>
<em>The equation of the Parabola ( h,k) = (6 , 6)</em>
<em>( y - k )² = 4 a ( x - h )</em>
<em>(y - 6 )² = 4 (2) (x -6)</em>
<em>(y - 6 )² = 8 (x -6)</em>
<u><em></em></u>
Answer:
$170,000 D. $800,000
Step-by-step explanation:
$170,000 D. $800,000
To factor,
<h2>
[[[</h2>
1) First multiply coefficient of a² and constant no,
That is,
3×(-42)=-126
Since the<u> resultant no is negative</u>, you should find two such factors of 126 <u>which</u> <u>will give us the coefficient of a (=11)</u> on subracting those factors.
2) Find the factor
126=2×3×3×7
=18×7
18 and 17 are factors of 126
Also,18-7 =11.
So they are required factors for factoring,
<h2>
]]]</h2>
Once you have understood above steps you can solve on your own. All you need to do is split 11 into factors ,take common terms and you will get answer.
<u>Answer:</u>
3a²+11a-42
=3a²+(18-7)a -42
=3a²+18a-7a-42
=3a(a+6) -7(a+6)
=(a+6)(3a-7)
Answer:
A.
Step-by-step explanation: